Hydrogen Sulfide Is a Novel Protector of the Retinal Glycocalyx and Endothelial Permeability Barrier - Allen, Claire L.; Wolanska, Katarzyna; Malhi, Naseeb K.; Benest, Andrew V.; Wood, Mark E.; Amoaku, Winfried; Torregrossa, Roberta; Whiteman, Matthew; Bates, David O.; Whatmore, Jacqueline L. (Frontiers in Cell and Developmental Biology, 2021)
Significantly reduced levels of the anti-inflammatory gaseous transmitter hydrogen sulfide (H2S) are observed in diabetic patients and correlate with microvascular dysfunction. H2S may protect the microvasculature by preventing loss of the endothelial glycocalyx. We tested the hypothesis that H2S could prevent or treat retinal microvascular endothelial dysfunction in diabetes. Bovine retinal endothelial cells (BREC) were exposed to normal (NG, 5.5 mmol/l) or high glucose (HG, 25 mmol/l) ± the slow release H2S donor NaGYY4137 in vitro. Glycocalyx coverage (stained with WGA-FITC) and calcein-labelled monocyte adherence was measured. In vivo, fundus fluorescein angiography (FFA) was performed in normal and streptozotocin-induced (STZ) diabetic rats. Animals received intraocular injection of NaGYY or the mitochondrial-targeted H2S donor AP39 (100 nM) simultaneously with STZ (prevention) or on day 6 after STZ (treatment) and the ratio of interstitial to vascular fluorescence was used to estimate apparent permeability. NaGYY prevented HG-induced loss of BREC glycocalyx, increased monocyte binding to BREC (p=<0.001) and increased overall glycocalyx coverage (p=<0.001). In rats the STZ-induced increase in apparent retinal vascular permeability (p=<0.01) was significantly prevented by pre-treatment with NaGYY and AP39 (p<0.05) and stabilised by their post-STZ administration. NaGYY also reduced the number of acellular capillaries (collagen IV+/IB4-) in the diabetic retina in both groups (p=<0.05). We conclude that NaGYY and AP39 protected the retinal glycocalyx and endothelial permeability barrier from diabetes-associated loss of integrity and reduced the progression of diabetic retinopathy (DR). H2S donors that target the glycocalyx may therefore be a therapeutic candidate for DR.